2017
DOI: 10.1017/s0960258517000095
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal effect of parental lines on the physiological potential and seed composition of corn hybrid seeds

Abstract: Obtaining corn hybrid seeds (Zea mays L.) with high vigour depends on the parental lines and the direction of the cross, and this relates to seed desiccation tolerance and composition. This research studied reciprocal crosses between pairs of proprietary, elite parent lines (L1 and L5; L2 and L4) producing hybrid seeds with different qualities attempting to correlate vigour with seed composition, focusing on storage proteins, starch and soluble sugar amounts. Four corn hybrid seed lots produced from reciprocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…A negative correlation between the total protein, total phosphorus, phytate and starch with physiological response of seeds also was found, and a negative correlation between germination and starch content (-0.63) and the total phosphorus content (-0.65) (Figure 4b). Similar results were found by Santos et al (2017), according these authors total protein and starch content are not correlated with vigour in maize seeds. Delgado et al, (2015), showing that the initial content of the reserve components was not the determining factor for the maintenance of the vigor in soybean seed.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…A negative correlation between the total protein, total phosphorus, phytate and starch with physiological response of seeds also was found, and a negative correlation between germination and starch content (-0.63) and the total phosphorus content (-0.65) (Figure 4b). Similar results were found by Santos et al (2017), according these authors total protein and starch content are not correlated with vigour in maize seeds. Delgado et al, (2015), showing that the initial content of the reserve components was not the determining factor for the maintenance of the vigor in soybean seed.…”
Section: Resultssupporting
confidence: 85%
“…The results of correlation between soluble sugar and vigor by accelerated aging test, suggest that higher initial content of soluble sugar contributes to higher vigor of seeds for VPA1 inbred line. Santos et al (2017) observed the ratio between the sum of oligosaccharides and the sum of the monosaccharide reducing sugars, presented a positive correlation with the accelerated ageing, cold test and seedling emergence in the field tests in maize. This result indicate that seeds with a higher initial content of soluble sugars could overcome the stress condition.…”
Section: Resultsmentioning
confidence: 80%
“…41 The conversion of the small, soluble carbohydrate pool from predominately reducing monosaccharides to predominately nonreducing sugar oligomers during orthodox seed maturation reduces the absolute number of these dissolved solutes, protects against Maillard reactions by tying up reducing ends in intermonosaccharide covalent bonds, and creates oligosaccharides capable of forming a glassy state conducive to the intracellular milieu withstanding desiccation. 42 Also, the relative abundance of sucrose to RFO appears to influence seed vigor. 2 The zmvp1-R mutant seed exhibits increased glucose and sucrose and decreased galactinol and raffinose, compared to that of WT, and has a viviparous phenotype (Figure 1B−D).…”
Section: ■ Discussionmentioning
confidence: 99%
“…Several reports noted differential expression between reciprocal F1 hybrids in maize for various kernel and germination traits (Cervantes Ortiz et al, 2007;Cabral et al, 2013;de la Torre and Biasutti, 2015;Santos et al, 2017;de Abreu et al, 2019). In Angiosperms, double fertilization results in the development of the diploid embryo and triploid endosperm that are surrounded by the maternal seed coat derived from the ovule integuments.…”
Section: Maizementioning
confidence: 99%